2021
DOI: 10.5603/cj.a2019.0019
|View full text |Cite
|
Sign up to set email alerts
|

Transfermoral aortic valve implantation using self-expanding New Valve Technology (NVT) Allegra bioprosthesis: A pilot prospective study

Abstract: Background: Transcatheter aortic valve implantation (TAVI) has become a standard therapeutic option for patients with severe aortic stenosis (AS) at high cardiac surgical risk. The aim of the NAU-TILUS study was to investigate the safety and performance of the New Valve Technology (NVT) Allegra bioprosthesis in high-risk patients undergoing TAVI. Methods: Twenty seven patients with severe, symptomatic AS at high surgical risk were prospectively enrolled, who underwent treatment using the novel self-expanding N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…Notably, the survival rate at 30 days was 100%; no coronary obstruction was detected. Mean gradients at discharge and at 30 days as assessed by an independent echocardiographic core lab (16.1±6.4 mmHg and 14.8±6.5 mmHg, respectively) and evaluated invasively post procedure (11.6±3.7 mmHg) were low for ViV procedures, albeit higher than those seen after TAVI in native aortic valves with the ALLEGRA THV 17,18,24 due to the smaller inner diameter of the surgical bioprosthetic valves.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Notably, the survival rate at 30 days was 100%; no coronary obstruction was detected. Mean gradients at discharge and at 30 days as assessed by an independent echocardiographic core lab (16.1±6.4 mmHg and 14.8±6.5 mmHg, respectively) and evaluated invasively post procedure (11.6±3.7 mmHg) were low for ViV procedures, albeit higher than those seen after TAVI in native aortic valves with the ALLEGRA THV 17,18,24 due to the smaller inner diameter of the surgical bioprosthetic valves.…”
Section: Discussionmentioning
confidence: 90%
“…There was one case (3.3%) with evidence of subclinical prosthetic valve thrombosis after 23 days under treatment with rivaroxaban, which was detected during the standard echo examination at the 30-day follow-up visit. The patient was without symptoms, and mean pressure gradients at discharge and 30 days (19 mmHg (indexed effective orifice area [EOAi] <0.65 cm 2 /m 2 ) at discharge, resulting in an overall device success rate of 60% (18).…”
Section: Thirty-day Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is no need for fast or rapid pacing during the implantation process. Data on this THV are limited and includes the first-in-human clinical studies showing results with a hemodynamic performance comparable to that of other THVs (25,26). Due to its hemodynamic properties, a potential use of this THV in valve-in-valve settings has been described (35).…”
Section: Acurate Neomentioning
confidence: 99%
“…The first-in-human clinical trial with implantations of the Allegra took place in 2013 by Wenaweser [2]. To date, several conducted studies showed encouraging short-term outcomes in treating patients with severe aortic native valve stenosis using NVT devices [2][3][4], but longer-term results are lacking. Herein, are presented one-year single-center results with the Allegra.…”
Section: Introductionmentioning
confidence: 99%